2002
DOI: 10.1097/00000421-200202000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-Induced Pulmonary Toxicity

Abstract: Gemcitabine is a pyrimidine analog with a similar chemical structure and mechanism of action, as cytarabine. It has been shown to be a highly active agent for non-small cell lung cancer, pancreatic cancer, urothelial cancer, breast cancer and ovarian cancer. Gemcitabine is relatively well tolerated and myelosuppression is the dose-limiting toxicity. Pulmonary toxicity with gemcitabine is relatively uncommon, but a well recognized entity, associated with significant morbidity and mortality. A high index of susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 15 publications
0
20
0
2
Order By: Relevance
“…In contrast, other studies have shown that the rate of grades 3–4 pneumonitis is similar across tumor types, but with more treatment-related deaths due to pneumonitis in patients with NSCLC 10,11,30. It is unclear why NSCLC may be associated with more pneumonitis and/or treatment-related deaths, but a number of hypotheses (while not yet studied) seem plausible, including higher rates of pre-existing adverse pulmonary conditions (i.e., tobacco exposure, previous lung radiation) and previous exposure to drugs associated with interstitial lung disease, including taxanes,31 epidermal growth factor receptor tyrosine kinase inhibitors,32,33 and gemcitabine 34…”
Section: Epidemiologymentioning
confidence: 99%
“…In contrast, other studies have shown that the rate of grades 3–4 pneumonitis is similar across tumor types, but with more treatment-related deaths due to pneumonitis in patients with NSCLC 10,11,30. It is unclear why NSCLC may be associated with more pneumonitis and/or treatment-related deaths, but a number of hypotheses (while not yet studied) seem plausible, including higher rates of pre-existing adverse pulmonary conditions (i.e., tobacco exposure, previous lung radiation) and previous exposure to drugs associated with interstitial lung disease, including taxanes,31 epidermal growth factor receptor tyrosine kinase inhibitors,32,33 and gemcitabine 34…”
Section: Epidemiologymentioning
confidence: 99%
“…The onset of drug-associated ILD during therapy for advanced NSCLC usually occurs within a few weeks of the start of treatment (Thomas et al , 2000; Gupta et al , 2002; Kudrik et al , 2002; Read et al , 2002). Indeed, retrospective analysis of the first 152 patients in Japan to experience gefitinib-associated ILD showed that >75% of cases occurred within 3 months, with the majority of these occurring within 4 weeks.…”
Section: Suspicion Of Drug-associated Ild In Patients With Nsclcmentioning
confidence: 99%
“…The symptoms of drug-associated ILD, as with all forms of the condition, include rapidly developing breathlessness and a dry and unproductive cough, together with fever (Thomas et al , 2000; Gupta et al , 2002; Kudrik et al , 2002; Read et al , 2002). Such symptoms are nonspecific and can occur with a large number of common illnesses often associated with NSCLC, or they may be due to cancer progression or lung cancer therapy.…”
Section: Suspicion Of Drug-associated Ild In Patients With Nsclcmentioning
confidence: 99%
“…The incidence of grade 4 lung toxicity ranges from 0.06%, as reported by an industry study based on commercial exposure, to 8%, as reported in several case study reviews, and the mortality rate is 20% [7,8]. In addition, gemcitabine-induced eosinophilic pneumonia has been reported previously [9,10].…”
Section: Case Presentationmentioning
confidence: 99%